The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1113/jphysiol.1992.sp019297
|View full text |Cite
|
Sign up to set email alerts
|

Crossed actions on group II‐activated interneurones in the midlumbar segments of the cat spinal cord.

Abstract: SUMMARY1. Evidence has been sought for crossed actions on midlumbar propriospinal neurones activated by ipsilateral group II muscle afferents, with particular emphasis on those neurones with projections to the ipsilateral hindlimb motor nuclei.2. A large majority of group II-activated midlumbar neurones were influenced by stimulation of contralateral group II afferents. The most frequent and most powerful actions were from those nerves which most effectively influenced ipsilateral midlumbar neurones. Crossed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…Considering that most midlumbar interneuron recipients from group II input are influenced by afferent fibres from both ipsilateral and contra-lateral sides 13 , a relation from ankle dorsiflexors during initial contact and loading response to contra-lateral knee extensors during pre swing could be expected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that most midlumbar interneuron recipients from group II input are influenced by afferent fibres from both ipsilateral and contra-lateral sides 13 , a relation from ankle dorsiflexors during initial contact and loading response to contra-lateral knee extensors during pre swing could be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies involving healthy subjects have demonstrated that the degree of plantar flexor activity during propulsion depends on the degree of muscle activity 9 and on the magnitude of the ground reaction force 10 of the contralateral limb during heel strike. This interlimb relation observed during step-to-step transition of unimpaired walking 9,10 , and also in standing-related tasks 11,12 , can be justified by the bilateral influence of group II fibres on spinal interneurons 13 and by the importance of vestibulo-and reticulo-spinal pathways on group II fibres 14 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the best understood mammalian circuits involved in such integration is concerned with reflexes evoked by activation of group II muscle afferents that have powerful and widespread actions on motoneurons (Matthews, 1972;Lundberg et al, 1987b). Recent studies have demonstrated that some group II actions on motoneurons are evoked disynaptically or trisynaptically and hence may be mediated by a pathway including only one or two interneurons (Edgley and Jankowska, 1987a;Lundberg et al, 1987a;Arya et al, 1991;Bajwa et al, 1992). The disynaptic actions of group II afferents have been shown to be evoked via interneurons located ipsilaterally in the intermediate zone and contralaterally in lamina VIII (Cavallari et al, 1987;.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusions obtained in each field combined could contribute more significantly to the construction of scientific knowledge about interlimb coordination. In fact, the importance of studying gait interlimb coordination is based on its impact on the metabolic cost of walking (Donelan, et al, 2002a;Donelan, Kram, & Kuo, 2002c;Kuo, Donelan, & Ruina, 2005;Kuo, et al, 2007), and is supported by biomechanical evidence (Donelan, et al, 2002a(Donelan, et al, , 2002cKuo, et al, 2007;Winter & Eng, 1995), and neurophysiological factors at the spinal (Bajwa, Edgley, & Harrison, 1992;Corna, Galante, Grasso, Nardone, & Schieppati, 1996;Dietz, 1992) and supraspinal levels (Drew, Prentice, & Schepens, 2004;Matsuyama et al, 2004).…”
Section: Introductionmentioning
confidence: 99%